A one-pot and modular self-assembly strategy for high-performance organized enzyme cascade bioplatforms based on dual-functionalized protein–PtNP@mesoporous iron oxide hybrid. Issue 1 (6th December 2018) - Liu, Yan; Qin, Yuling; Zheng, Yuanlin; Qin, Yong; Cheng, Mengjun; Guo, Rong
Abstract : A one-pot and modular self-assembly strategy for high-performance enzyme cascade bioplatform based on dual-functionalized protein/inorganic hybrid. Abstract : Inspired by the delicate structure and prominent efficiency of natural multiple-enzyme systems, combining nanotechnologies such as nanomaterials, self-assemblies, and enzyme mimics is fascinating for the development of next-generation high-performance organized enzyme cascade bioplatforms. In our facile and convenient design, a dual-functionalized β-casein-Pt nanoparticles@mesoporous-Fe3 O4 (CM-PtNP@m-Fe3 O4 ) hybrid acts as both a nanozyme with outstanding peroxidase-like activity and a scaffold to immobilize and stabilize a natural oxidase, resulting in a high-performance organized enzyme cascade bioplatform for a one-pot assembly procedure. Owing to special physicochemical surface properties, the multipoint attachment of various interactions between natural enzymes and protein/inorganic hybrids leads to efficient immobilization of the enzyme with retained activity. The proposed cascade bioplatform provides superior cholesterol sensing, including simplicity (one-step detection), reusable enzymes (peroxidase mimic and oxidase), and excellent sensitivity (detection limit, 0.05 μM). To our knowledge, the bioplatform presented in this work shows the highest sensitivity for cholesterol detection among all reported colorimetric methods based on nanozymes. Therefore, the highly rationally designed protein/inorganic hybrid and dual-functional strategy used in this study will provide a facile one-pot and effective high-performance organized enzyme cascade bioplatform with potential applications in biosensing, biotransformation, decontamination, and biofuel.